Privatization in Africa : The Zambian Example - Emile Sawaya (World Bank, Washington, DC, 2012)
The Note analyzes Zambia's reasons, and measures for success in privatization. It stipulates the following key indicators for assessing the performance of divestiture programs in Africa: the extent of divestiture; fiscal impact; the efforts made, and achievement in broadening ownership; the level of foreign direct investment attracted; enterprise post-privatization performance; the depth and quality of program design and management; and, transparency and government commitment. Of these, Zambia rates medium to high on all indicators, and the note outlines that commitment is what gave prominence to the private sector's role in the process. However, the privatization program has not been without its problems. Because of its fragile economic situation, the country was not readily attractive to foreign investors; but, multinational companies who have invested in Zambia are impressed with the way the program is being managed. As a result, the country is now one of the most attractive to investors in Africa.